(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Nechiporenko K. Intellectual and creative skills in the structure of a future elementary school teacher. Тhe article analyses the content of the intellectually-creative skills and groundes their place in the structure of personality of future teachers of elementary school.